Models of Economic Growth and Economic Crisis - Truong Hong , Trinh; Truong Ba , Thanh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2022)
This paper reviews the theories of economic growth and economic crisis, in which microfoundation and financial system are the major challenges in the current models of economic growth and economic crisis. For these reasons, this paper aims to develop a theoretical models to explain the general equilibrium mechanism and steady-state growth path in relation to the inflation-unemployment curve. From this base, the paper integrates financial system into the general equilibrium framework to conduct the relationship between economic growth and economic crisis. The paper contributes theoretical foundation for further research on economic growth and economic crisis.
Keywords: Economic growth; Economic crisis; Microfoundation; Financial system; General equilibrium